2016
DOI: 10.1539/joh.15-0152-oa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and social connection on perceived anxiety over radiation exposure among decontamination workers in Fukushima Prefecture, Japan

Abstract: Objectives: To reveal the effect of age and other factors on perceived anxiety over radiation exposure among decontamination workers in Fukushima Prefecture, Japan. Methods: A survey questionnaire was sent to 1505 workers, with questions regarding age, presence of a written employment contract, previous residence, radiation passbook ownership, presence of close persons for consultation, knowledge of how to access public assistance, and a four-point scale of radiation-related anxiety (1= "Very much," 2= "Somewh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 10 publications
2
25
1
Order By: Relevance
“…Regarding participant characteristics, age 50-59 years was the most common category, which is consistent with the results of past studies of OLs [12] and radioactivity decontamination workers [13,14,[16][17][18]. For the acquisition of the knowledge, the answer pattern "incorrect to correct" was the second most common in working environment management and control of operations, suggesting the effectiveness of the training session.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding participant characteristics, age 50-59 years was the most common category, which is consistent with the results of past studies of OLs [12] and radioactivity decontamination workers [13,14,[16][17][18]. For the acquisition of the knowledge, the answer pattern "incorrect to correct" was the second most common in working environment management and control of operations, suggesting the effectiveness of the training session.…”
Section: Discussionsupporting
confidence: 87%
“…("present" or "absent"). Our previous study indicated that the presence of close persons to confide in may ease anxiety over radiation exposure 11) , and we then assumed that the presence of a close person to confide in may also be associated with anxiety over lack of privacy. Thus, this question was included in the questionnaire.…”
Section: Methodsmentioning
confidence: 97%
“…The study subjects were the same male radiation decontamination workers used in our previous studies 10,11) .In total, 1505 workers were recruited from companies involved in radiation decontamination work in Fukushima Prefecture, and attended a training program held by the Fukushima Occupational Health Promotion Center in 2013 to help prevent radiation exposure. Selfadministered questionnaires were sent to the workers' companies, to be distributed among all 1505 workers.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-rater consistency was acceptable (κ = 0.72, p < 0.001). Evaluation of the full text against the eligibility criteria left 19 articles [ 7 , 11 , 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] in the final review. Another three articles [ 32 , 33 , 34 ] were found by hand-searching of the reference lists of the 19 articles.…”
Section: Methodsmentioning
confidence: 99%